Determining Plasmaspheric Density From the Upper Hybrid Resonance and From the Spacecraft Potential: How Do They Compare?. Issue 3 (20th March 2020) - Jahn, J.‐M.; Goldstein, J.; Kurth, W. S.; Thaller, S.; De Pascuale, S.; Wygant, J.; Reeves, G. D.; Spence, H. E.
Abstract: The plasmasphere is a critical region of the magnetosphere. It is important for the evolution of Earth's radiation belts. Waves in the plasmasphere interior (hiss) and vicinity (electromagnetic ion cyclotron, chorus) help control the acceleration and loss of radiation belt particles. Thus, understanding the extent, structure, content, and dynamics of the plasmasphere is crucial to understanding radiation belt losses. The Van Allen Probes mission uses two methods to determine the total plasma density. First, the upper hybrid resonance frequency can provide electron density; this determination is the most accurate and robust. However, it requires significant analysis and is challenging during geomagnetically active times: It becomes difficult to interpret the wave spectrum, and the amount of available data is severely limited. Second, the spacecraft potential is a proxy for the plasma density. These high‐resolution measurements are available with high duty cycle. However, environmental effects can limit the accuracy of this method. The relation between spacecraft potential and density is empirical, requiring an independent density measurement and repeated checks. We perform a quantitative comparison of these two in situ techniques during the first 3.5 years of the Van Allen Probes mission. We show how to calibrate potential‐based density measurements using only publicly available wave‐derived densities to provide high‐fidelity results even if upper hybrid measurements are sparse or unavailable. We quantify the level of uncertainty to expect from potential‐derived density data. Our approach can be applied to any in situ spacecraft mission where reliable absolute density and spacecraft potential data are available. Key Points: We compare Van Allen Probes total plasma densities derived from spacecraft potential and from upper hybrid resonance wave measurements We present a method to easily calibrate spacecraft potential‐derived plasma densities during the mission We quantify the uncertainties of potential‐derived plasma densities that remain after applying this calibration